CRITICAL REVIEW ON WOMEN IN INDIAN CIVILIZATION WITH SPECIAL REFERENCE TO ANCIENT AND MEDIEVAL INDIA (Journal of Namibian Studies : History Politics Culture, 2023)
The goal and nature of social reform movements in the nineteenth century were changed in the early twentieth century by the critical outlook that educated Indians developed, who imitated western societies and made arguments using western cultural norms even though they had little application to India and her civilization. Due to the ease with which a woman can obtain a divorce at her whim and pleasure, people in the west have put themselves up as ideals in front of Indian women in an attempt to highlight the injustices meted out to Indian women in comparison to the freedom experienced by women in the east. In this article, review on women in Indian civilization with special reference to ancient and medieval India has been discussed.